Falsafah Ibadat dan Hubungan Manusia - Tuhan - Idris bin Zakaria (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Not only are the religious worships obligated to every mukallaf Muslim as the  sign or evidence of a faithful servant of Allah, or as the proof of Allah's existence, but  these practices have their own foundation and philosophy. Both foundation and philosophy  of the religious practices are intended to raise the level and status of human beings as the  best creation of God compared to all other creatures. Worship needs to be practiced  consistently and frequently so that it reinforces and intensifies the remembrance of God in  the heart of human. The article concludes that obedient servants who always practice the  religious worships will return to their original nature as pure and holy human, and will  reach their position as the best creation of God.